Understanding the Temperature‐Responsive Self‐Assemblies of Amphiphilic Random Copolymers by SANS in D2O Solution. Issue 5 (5th February 2021) - Domenici, Fabio; Guazzelli, Elisa; Masotti, Elena; Mahmoudi, Najet; Gabrielli, Sara; Telling, Mark T. F.; Martinelli, Elisa; Galli, Giancarlo; Paradossi, Gaio
Abstract: The self‐assembly behavior, in aqueous solution, of amphiphilic methacrylic random copolymers with perfluoroalkyl and polyoxyethylene side chains and the morphology of the resulting nanostructures are investigated by small‐angle neutron scattering (SANS). The results allow to clarify the effect of temperature on the self‐assembly features of copolymers and the structural morphology of both unimer single‐chain entities and larger multi‐chain aggregates of unimers. Shape, flexibility, and size of the aggregates are proved to be modulated by temperature and copolymer composition. The existence of three distinct phases of self‐assembled structures is pointed out as a function of increasing temperature: 1) globular unimers; 2) coexistence of extended unimers and aggregates; and 3) aggregates, which overall show full reversibility in a wide range of copolymer concentrations. Abstract : The work sheds new light on the assembling in water of two amphiphilic random copolymers from hydrophobic 2‐(perfluorohexyl)ethyl acrylate (FA) and hydrophilic poly(ethylene glycol) methyl ether methacrylate (PEGMA) at two different PEGMA/FA mole ratios. Small‐angle neutron scattering measurements reveal three distinct and reversible phases of self‐assembled structures depending on temperature: 1) globular unimers; 2) coexistence of extended unimers and aggregates; and 3) aggregates.